"Every Tone Was a Testimony": Black Music, Literature, and Law. (February 2016) - Brown, Christopher Michael
The music that chronicles the African American experience is marked in profound but subtle and contradictory ways by the law, perhaps the most pervasive presence in black life since enslaved Africans arrived in the New World. From the mournful but veiled complaints of the sorrow songs to Jay Z's boastful narration of a pretextual traffic stop, at the heart of so much of the music of black culture lies a wary appraisal, and often an outright rejection, of the "justice" of American law. This Commentary reviews the fraught relationship between the law and the tradition of African American music.